Patient-Specific Alterations in CO2 Cerebrovascular Responsiveness in Acute and Sub-Acute Sports-Related Concussion - Mutch, W. Alan C.; Ellis, Michael J.; Ryner, Lawrence N.; McDonald, Patrick J.; Morissette, Marc P.; Pries, Philip; Essig, Marco; Mikulis, David J.; Duffin, James; Fisher, Joseph A. (Frontiers in Neurology, 2018)
Background: Preliminary studies suggest sports-related concussion (SRC) is associated with alterations in cerebral blood flow (CBF) regulation. Here, we use advanced magnetic resonance imaging (MRI) techniques to measure CBF and cerebrovascular responsiveness (CVR) in individual SRC patients and healthy control subjects. Methods: Fifteen SRC patients (mean age=16.3, range 14-20 years) and 27 healthy control subjects (mean age=17.6, range 13-21 years) underwent anatomical MRI, pseudo-continuous arterial spin labeling (pCASL) MRI and model-based prospective end-tidal targeting (MPET) of CO2 during blood oxygenation level-dependent (BOLD) MRI. Group differences in global mean resting cerebral blood flow (CBF) were examined. Voxel-by-voxel group and individual differences in regional CVR were examined using statistical parametric mapping (SPM). Leave-one-out receiver operating characteristic curve analysis was used to evaluate the utility of brain MRI CO2 stress testing biomarkers to correctly discriminate between SRC patients and healthy control subjects. Results: All studies were tolerated with no complications. Traumatic structural findings were identified in one SRC patient. No significant group differences in global mean resting CBF were observed. There were no significant differences in the CO2 stimulus and O2 targeting during BOLD MRI. Significant group and patient-specific differences in CVR were observed with SRC patients demonstrating a predominant pattern of increased CVR. Leave-one-out ROC analysis for voxels demonstrating a significant increase in CVR was found to reliably discriminate between SRC patients and healthy control subjects (AUC of 0.879, p=0.0001). The optimal cut-off for increased CVR declarative for SRC was 1899 voxels resulting in a sensitivity of 0.867 and a specificity of 0.778 for this specific ROC analysis. There was no correlation between abnormal voxel counts and PCSS scores among SRC patients. Conclusions: Acute and sub-acute sports-related concussion is associated with alterations in CVR that can be reliably detected by brain MRI CO2 stress testing in individual patients.